Foster groups: Systematization of a participatory model for the diagnostic and therapeutic formulation in a community mental health center. Chorrillos-Peru, 2018 - Castillo-Martell, Humberto (2021)
Objective: To systematize the process of diagnosis and treatment plan formulations in participatory groups of users and professionals, called Fostering Groups, as an alternative to the conventional model of individual and sequential psychiatric consults, in the field of community mental health.   Material and Methods: The study was carried out in a community mental health center (CMHC) in Lima throughout the period January-December 2018. An action-research methodology was followed, in which proposals arising from the experiences were put into action to, then, critically analyze the and adjust them successively until reaching a point of standardization or consensus among the participants. Results: The participatory model was applied in 97% of the users during the observation period and the formulation of diagnoses and treatment plans during the Foster Group session was successfully reached in 85% of the patients. The sessions were standardized in four concatenated and semi-structured moments: Horizontal presentation of participants, mutual empathetic understanding, collective exploration of causes, and shared therapeutic decisions. Conclusions: The Fostering group model was a viable and effective alternative for the initial formulation of diagnoses and therapeutic plans in the CMHC, with semi-structured phases conveniently standardized and replicable.